Tolerance as an imperative for higher education and democracy - Davids, N. (South African Journal of Higher Education, 2019)
Beyond the noise and din of the numerous #feesmustfall campaigns, there arose deeper concerns of the lack of regard on display not only between protesters and institutional authorities, but between protesting and non-protesting students. Of course, protests by their nature are manifestations of perceivably unheard and unrecognised demands and plights, which make the flaring of tempers inevitable. But, perhaps, what defined the student protests most distinctly were not the impassioned calls for economic accessibility, transformation, and decolonisation, but its volatility, and, at times, sheer contempt. The concern of this article is to offer a conceptual consideration of tolerance as an educational imperative within higher education, and democracy. That is, if higher education is to fulfil its responsibility in relation to the public good, then it has to espouse those virtues that are most likely to contribute to peaceful and harmonious co-existence.